Joko Widodo Dalam Bingkai Harian Umum Republika - Suharyo Suharyo (Program Studi Sastra Indonesia, Fakultas Ilmu Budaya, Universitas Diponegoro, 2017)
This study aims to describe how the daily Republika frames President Joko Widodo. To disclose, simak method followed by noting technique – as described by Sudarjanto (1993) – will be used, while the framing model by Pan Kossicki will be used for the analysis. As a result, President Joko Widodo is positively framed through (a) a syntactic structure that includes the title diction he chooses, leads, backgrounds, source uses, and positive news cover; (B) structure of the script making full use of the 5W 1H element, (3) the thematic structure seen through President Joko Widodo's message which is packed with a polite diction, such as